The Impact of STEM-Integrated Teaching Factory Student Worksheets on Vocational School Students' Entrepreneurial Readiness - Findayani, Zulia; Syukri*, Muhammad; Susilawati, Susilawati; Khaldun, Ibnu; Maghfirah, Siti; Mulhadi, Mulhadi; Ulfa, Zuchra; Arsad, Nurazidawati Mohamad (Universitas Syiah Kuala, 2025)
The high unemployment rate among vocational school graduates, which reached 8.62%, reflects the gap between the purpose of establishing vocational schools as a creator of skilled labor and the real conditions in the field. This study aims to analyze the effect of using student worksheets (LKPD) based on the teaching factory model integrated with the science, technology, engineering, and mathematics (STEM) approach on the entrepreneurial readiness of vocational school students.Using a quantitative approach with a pretest-posttest design in a single group, this study involved eleventh-grade students majoring in electrical installation, focusing on solar power installation materials. The research instrument was an entrepreneurial readiness questionnaire covering six key indicators: self-confidence, task and result orientation, risk-taking, leadership, originality, and entrepreneurial readiness. The analysis results showed that the data were normally distributed based on the normality test with a value 0.05. Furthermore, the T-test results showed a significance value of 0.001, indicating a significant difference before and after the treatment. All indicators of entrepreneurial readiness significantly increased, with an average N-Gain score of 0.85, categorized as high. These findings confirm that the teaching factory-based learning model integrated with STEM is effective in improving students' practical skills, conceptual understanding, and readiness to face the workforce and build independent businesses. Therefore, this study recommends using teaching factory-based LKPD integrated with STEM as an innovative learning medium to enhance vocational students' entrepreneurial competencies